The strategic function of the library in enhancing educational activities at SMAN 3 Garut - Muhammad Subhan Zaenul Rofi; Angga Hadiapurwa (Himpunan Pengembang Kurikulum Indonesia, 2025)
The digital era demands that school libraries adapt to support effective learning processes, necessitating that the SMAN 3 Garut library optimize its role as a learning resource center aligned with modern educational needs. This research aims to analyze library strategies that support teaching and learning at SMAN 3 Garut and to identify the challenges faced and the development efforts undertaken. The study employs a qualitative approach, using interviews and direct observation to collect data on library services, collections, and strategies. The research findings indicate that the library maintains collections of printed materials, including textbooks, reference works, and general-interest titles, and operates a membership-based borrowing system, with management conducted manually and semi-digitally. The library actively provides alternative study spaces and collaborates closely with teachers in designing literacy activities. Main challenges include low student interest in reading and limited resources; however, strategies such as establishing reading ambassadors and cross-role collaboration have been implemented to address these issues. In conclusion, SMAN 3 Garut library plays a strategic role in supporting learning through various service innovations. However, further development of digital facilities is needed to ensure that the learning resource center remains adaptable and relevant to contemporary developments. Abstrak Era digitalisasi menuntut perpustakaan sekolah untuk beradaptasi dalam mendukung proses pembelajaran yang efektif, sehingga perpustakaan SMAN 3 Garut perlu mengoptimalkan perannya sebagai pusat sumber belajar yang relevan dengan kebutuhan pendidikan modern. Penelitian ini bertujuan untuk menganalisis strategi perpustakaan dalam mendukung proses belajar mengajar di SMAN 3 Garut serta mengidentifikasi tantangan dan upaya pengembangan yang dilakukan. Penelitian menggunakan pendekatan kualitatif dengan teknik wawancara dan observasi langsung untuk mengumpulkan data mengenai layanan, koleksi, dan strategi perpustakaan. Hasil penelitian menunjukkan bahwa perpustakaan menyediakan koleksi bahan pustaka berupa buku cetak yang mencakup buku pelajaran, referensi, dan literasi umum dengan sistem peminjaman berbasis keanggotaan. Pengelolaan dilakukan secara manual dan semi-digital. Perpustakaan berperan aktif menyediakan ruang belajar alternatif dan menjalin kerja sama dengan guru dalam merancang kegiatan literasi. Tantangan utama meliputi rendahnya minat baca murid dan keterbatasan sumber daya, namun telah dilakukan strategi pembentukan duta baca dan kolaborasi lintas peran untuk mengatasinya. Kesimpulannya, perpustakaan SMAN 3 Garut berperan strategis dalam mendukung pembelajaran melalui berbagai inovasi layanan, meskipun masih perlu pengembangan fasilitas digital untuk menjadi pusat sumber belajar yang adaptif dan relevan dengan perkembangan zaman. Kata Kunci: perpustakaan sekolah; sekolah menengah atas; sumber belajar